The prognosis of early-stage breast cancer in extremely young female patients. Issue 1 (8th January 2021) - Chung, Wei-Pang; Lee, Kuo-Ting; Chen, Ya-Ping; Hsu, Ya-Ting; Loh, Zhu-Jun; Huang, Chien-Chang; Hsu, Hui-Ping
Abstract : Abstract: Breast cancer at a young age is associated with poor outcomes. However, few reports have compared the outcomes of breast cancer between extremely young patients and elderly patients. We retrospectively collected information on patients diagnosed with breast cancer before 30 years of age. This case-control study employed matched operative methods, stage, and subtypes with a case-to-control ratio of 1:3. The primary endpoint was disease-free survival, and the secondary endpoint was overall survival. We analyzed potential prognostic factors in univariate and multivariate analyses. This analysis included 18 patients in the young group with a median age of 28.5 years and 54 patients in the control group with a median age of 71 years. The 5-year disease-free survival rate was 68.8% in the former group and 84.6% in the latter group (P = .080). The 5-year overall survival was 87.1% and 91.2% in the young and old groups, respectively ( P = .483). Multivariate analysis showed that tumor size and triple-negative breast cancer was major prognostic factors of poorer disease-free survival in the young group. Extremely young breast cancer patients had a trend to develop a poorer disease-free survival than old patients, but not a poorer overall survival. Aggressive treatment for young patients at early stages of disease would improve survival.